A Study on Role of Education in Women Empowerment among Higher Secondary School Students - V, Shobitha; Selvakumar, Y Stanly (Journal of Advanced Research in English & Education; Vol 7 No 3 (2022): Journal of Advanced Research in English and Education, 2022)
Although women constitute half of the total population the society, yet they are lagging behind socially, economically and politically than men. Holistic development and progress of a society and a nation cannot be possible without development of the other half of the society. Hence, whole world is concern about the women empowerment.  Empowerment stands for transformation of people, their life and status, which includes the basic needs, economic security, capacity building, skill formation Participation in the decision-making process and above all a dignified social existence. Hence, to be empowered women need awareness, involvement and decision-making ability towards different social, economic and political issues. Empowerment has many facets, in the present study, the investigator considers three important facets of empowerment such as social, economic and political empowerment. Women ‘s self-confidence and self-esteem are strongly influenced by the education. Multiple studies were conducted and made a consensus that so long as women remain depressed and exploited, no nation can enjoy freedom and justice. When they are denied the opportunities for utilizing their complete potential, the economic parameter like growth, welfare and development remains undefined. So various steps were taken to define the concept the role of education in women empowerment and to find out ways through which women can be empowered (Dr.Amrita Joshi, 2012). So, one such way is education. Therefore, the author felt the need to review the different aspects pertaining to the empowerment. The problem is stated as Role of education in women empowerment among higher secondary school students. How to cite this article: Shobitha V, Selvakumar YS. A Study on Role of Education in Women Empowerment among Higher Secondary School Students. J Adv Res Eng & Edu 2022; 7(3): 5-8. DOI: https://doi.org/10.24321/2456.4370.202205